How surgeons make decisions when the evidence is inconclusive. - Hageman, Michiel G J S; Guitton, Thierry G; Ring, David (J Hand Surg Am, 2013)
PURPOSE: To address the factors that surgeons use to decide between 2 options for treatment when the evidence is inconclusive. METHODS: We tested the null hypothesis that the factors surgeons use do not vary by training, demographics, and practice. A total of 337 surgeons rated the importance of 7 factors when deciding between treatment and following the natural history of the disease and 12 factors when deciding between 2 operative treatments using a 5-point Likert scale between "very important" and "very unimportant." RESULTS: According to the percentages of statements rated very important or somewhat important, the most popular factors influencing recommendations when evidence is inconclusive between treatment and following the natural course of the illness were "works in my hands," "familiarity with the treatment," and "what my mentor taught me." The most important factors when evidence shows no difference between 2 surgeries were "fewer complications," "quicker recovery," "burns fewer bridges," "works in my hands" and "familiarity with the procedure." Europeans rated "works in my hands" and "cheapest/most resourceful" of significantly greater importance and "what others are doing," "highest reimbursement," and "shorter procedure" of significantly lower importance than surgeons in the United States. Observers with fewer than 10 years in independent practice rated "what my mentor taught me," "what others are doing" and "highest reimbursement" of significantly lower importance compared to observers with 10 or more years in independent practice. CONCLUSIONS: Surgeons deciding between 2 treatment options, when the evidence is inconclusive, fall back to factors that relate to their perspective and reflect their culture and circumstances, more so than factors related to the patient's perspective, although this may be different for younger surgeons. CLINICAL RELEVANCE: Hand surgeons might benefit from consensus fallback preferences when evidence is inconclusive. It is possible that falling back to personal comfort makes us vulnerable to unhelpful commercial and societal influences.
Keywords: Clinical Competence; Decision Making; Evidence-Based Medicine; Female; Hand; Humans; Male; Mentors; Orthopedics; Practice Guidelines as Topic